Gold Rush Girl - Avi 1937- (Somerville, Massachusetts : Candlewick Press, 2020)
"Victoria Blaisdell longs for independence and adventure, and she yearns to accompany her father as he sails west in search of real gold! But it is 1848, and Tory isnt even allowed to go to school, much less travel all the way from Rhode Island to California. Determined to take control of her own destiny, Tory stows away on the ship. Though San Francisco is frenzied and full of wild and dangerous men, Tory finds freedom and friendship there. Until one day, when Father is in the gold fields, her younger brother, Jacob, is kidnapped. And so Tory is spurred on a treacherous search for him in Rotten Row, a part of San Francisco Bay crowded with hundreds of abandoned ships."--Provided by publisher.
Keywords: Frontier and pioneer life -- Juvenile fiction -- California; Young women -- Juvenile fiction; Kidnapping -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Adventure stories; Frontier and pioneer life -- Fiction -- California; Young women -- Fiction; Kidnapping -- Fiction; Brothers and sisters -- Fiction; Adventure and adventurers -- Fiction; California -- Juvenile fiction -- Gold discoveries; California -- Juvenile fiction -- History -- 1846-1850; California -- Fiction -- Gold discoveries; California -- Fiction -- History -- 1846-1850; Historical fiction; Action and adventure fiction